Gentrificación en el Centro Histórico de Lima. Estudio de caso: gestión de la Municipalidad Metropolitana de Lima 2011-2014, en el sector de Barrios Altos que pertenece al área inscrita en la lista del Patrimonio Cultural de la Humanidad - Roldán Villanueva, Omar (2021)
The proposed research focuses on showing the evidence of the gentrification process, within a specific moment: Metropolitan municipal management of Lima 2011-2014, although it does not focus on studying management itself, as this article is part of a larger study - a master’s thesis-, what the article seeks is to show the evidence of gentrification within a sector of the Historical Center of Lima, located in the monumental area of Barrios Altos, as well as analyze the data presented contrasting theoretical postulates on gentrification with reality social, economic and architectural study area. The research focuses on the postulate that in Barrios Altos (delimited sector of study), an urban process is taking place that has visible elements, which are based on a metropolitan economic development that affects the population and real estate.